If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+13/9=4
We move all terms to the left:
x+13/9-(4)=0
determiningTheFunctionDomain x-4+13/9=0
We multiply all the terms by the denominator
x*9+13-4*9=0
We add all the numbers together, and all the variables
x*9-23=0
Wy multiply elements
9x-23=0
We move all terms containing x to the left, all other terms to the right
9x=23
x=23/9
x=2+5/9
| -8x(-3+4)+10x-2x+3=0 | | -x-(3x+4)/2=3 | | (7+4x)/2=(5x-2)+2/3 | | 7x+5x=54 | | 9=-3-y÷6 | | 4x+(5-1)=3(x-2)-7x | | 3x-2-5x=-8x+10 | | 6*8=0.125x | | k+2/3=4 | | 56-x+11=48 | | 5(h-3)=2(h+3) | | 1/x+2/3x=5 | | 4x2+3x-8=0. | | (Q-4)x5=30 | | -113(b+5)=7 | | 7x/(5x+8)=7/9 | | p+8=14.1p | | –2(u–7)=18 | | -6.3n=-25.2n | | –5(z–4)=35 | | 61=5s+11 | | 2/3y+11=-1/3y+8 | | y=1.05^20 | | -8+3x=-16+-13x | | 2x+2x+1x+1x+1x=40 | | 5–(x-2)=4x+17 | | 3m+7-2=8 | | 5-2x=3+x-43x | | 10w=4w+18 | | 10w=(4w+18)/4w | | x=0.25x(-4)x(-1) | | 3(x+3)=6x+1-3x |